Schizophrenia and attendance in primary healthcare: a population-based matched cohort study. (3rd July 2019) - Nørgaard, H. C. B.; Schou Pedersen, H.; Fenger-Grøn, M.; Vestergaard, M.; Nordentoft, M.; Laursen, T. M.; Mors, O.
Abstract: Objective: Schizophrenia is associated with high mortality, somatic comorbidity and reduced life expectancy. The general practitioner (GP) plays a key role in the treatment of mental and physical multimorbidity. Nevertheless, it is unclear how much individuals with schizophrenia use primary healthcare. This study aims to investigate the yearly numbers of consultations in general practice for individuals with schizophrenia. Design and Setting: We performed a population-based matched cohort study of 21, 757 individuals with schizophrenia and 435, 140 age- and gender-matched references from Danish National Registers. Monthly general practice consultations were analysed using a generalized linear model with log link and assuming negative binomial distribution. Main outcome measures: Consultation rates in general practice up to17 years after index diagnosis. Results: Individuals with schizophrenia attended their GP more than references throughout the study period. The cases had 82% (95% CI: 78-87) and 76% (95% CI: 71-80) more consultations in primary care after 1 year and 5 years, respectively. Individuals with both schizophrenia and comorbid somatic illness attended even more. Conclusion: Individuals with schizophrenia are in regular contact with their GP, especially if they have comorbid illnesses. Whether an average of six consultations per year for individuals with schizophrenia is sufficient is up for debate. The study demonstrates a potential for an increased prevention and treatment of individuals with schizophrenia in general practice. KEY POINTS: Schizophrenia is associated with high mortality, somatic comorbidity and reduced life expectancy. Little is known about the attendance pattern in primary care for individuals with schizophrenia. We found high attendance rates in primary care for individuals diagnosed with schizophrenia from index diagnosis and at least 17 years after diagnosis, which suggests opportunities for earlier intervention to improve their somatic health. We found an association between high illness comorbidity and increased risk of not attending the general practitioner. The most severely somatically and mentally ill individuals may thus be difficult to reach and support in the current healthcare system.